OPTIMIZATION OF CULTURE CONDITONS FOR THE PRODUCTION OF PRODUCTION OF β-MANNANASE FROM AN AGAR UTILIZING PAENIBACILLUS SP. MSL-9 - SANGANKAL MANJULA; MANOHAR SHINDE; JUNNA LALITHA (The Bioscan, 2010)
An agar utilizing Paenibacillus sp. MSL-9 from marine water was acclimatized to mannans for production of β-mannanase. The mannanase production was optimum at 44-48 h of incubation (0.74U/mg) in minimal mineral salts medium containing guar gum (0.3%, w/v) as carbon source, and combination of sodium nitrate (0.15% (w/v) and beef extract (0.15%, w/v) as a nitrogen source, at 30ºC and pH 8.0 respectively. The β-mannanase was inducible by mannan polymers. Simple sugars did not induce the enzyme and also suppressed the enzyme production when co-supplemented along with the mannans. Utilization of various agro-industrial wastes on mannanase production was also evaluated.